2019
DOI: 10.4103/jpbs.jpbs_25_19
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of ocular injuries, conjunctivitis and musculoskeletal disorder–related issues as occupational hazards among dental practitioners in the city of Salem: A randomized cross-sectional study

Abstract: Background: Similar to several other occupations, dentists are also stricken by bounteous occupational health hazards (OHHs) such as musculoskeletal disorders (MSDs) and ocular health–related issues. Aims: The aim of this study was to evaluate the diffusion of MSDs and ocular health–related issues among dental surgeons in Salem city, Tamil Nadu, India, according to age, sex, and number of practicing hours per week. Objectives: A survey was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
1
3
0
4
Order By: Relevance
“…The 12-month prevalence of MSDs in the hand varies between 25.0% and 49.7% [4,9,[11][12][13][18][19][20]. Other international studies report hand complaints ranging from 8.4% to 66.7% [8,14,15,[21][22][23][24]. Other research showed that 19.2% to 50.0% of dental students develop MSDs on the hand during their studies [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The 12-month prevalence of MSDs in the hand varies between 25.0% and 49.7% [4,9,[11][12][13][18][19][20]. Other international studies report hand complaints ranging from 8.4% to 66.7% [8,14,15,[21][22][23][24]. Other research showed that 19.2% to 50.0% of dental students develop MSDs on the hand during their studies [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Del mismo modo, Revankar et al . 33 determinaron que los cirujanos dentales con horarios de trabajo de 6-8 h/día fueron el 54,35%, mientras que el 22,46% realizó su trabajo durante 1-5 h/día, el 23,06% trabajó durante 9-12 h/día y solo el 1,05% trabajó 12 h/día. Igualmente, Azodo 34 informa que la incidencia de lesiones oculares se asoció con la edad, el uso de lentes de protección y los años de práctica.…”
Section: Discussionunclassified
“…Por ello, Lietz 39 recomienda el uso de sillón dental ergonómico con aumento, en comparación con sillones convencionales sin aumento, debido a que los primeros podrían soportar mejor la región lumbar y mantener la curvatura de la espalda baja. Revankar 33 , en su estudio, señala que el 94,68% de los odontólogos prefiere trabajar sentado y el 24,56%, la posición de pie.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Most of the injuries reported by dentists are usually of musculoskeletal in nature. 12 The stiffness of neck and bending of posture to enhance work efficacy can result into a lot of potential permanent risk changes. 13 With multiple treatment options, different chemicals being used and also constant contact with blood and oral tissues; the dental staff is always at a greater risk of nosocomial infections.…”
Section: Discussionmentioning
confidence: 99%